Preparation method of graphite negative electrode material, negative electrode plate and battery

By adding quinoline insolubles to the graphite anode material preparation process to optimize the embedded structure, the problem of high expansion rate of graphite anode material was solved, and the cycle performance and high-temperature storage performance were improved, providing a low-cost solution.

CN119349569AActive Publication Date: 2025-01-24JIANGSU TIANHE ENERGY STORAGE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411908887.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Existing graphite anode materials have a high expansion rate during cycling, which leads to rapid degradation of cycling performance. Furthermore, traditional modification methods suffer from high production costs or deterioration of high-temperature storage performance.

Method used

In the preparation of graphite anode materials, quinoline insolubles are added as additives to optimize the mosaic microstructure, form fine mosaic coke products, reduce the expansion rate, and prepare low-expansion graphite anode materials through high temperature and high pressure and graphitization treatment.

Benefits of technology

It significantly improves the cycle performance and high-temperature storage performance of graphite anodes, reduces production costs, and has a simple and efficient process, making it suitable for alkali metal ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349569A_ABST
    Figure CN119349569A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alkali metal ion batteries, and particularly provides a preparation method of a graphite negative electrode material, a negative electrode plate and a battery. The preparation method of the graphite negative electrode material comprises the following steps: mixing asphalt and a quinoline insoluble substance to form an asphalt mixture; and heating the asphalt mixture to obtain the graphite negative electrode material. In the coking process, the quinoline insoluble substance is used as an additive, the content of the quinoline insoluble substance in the asphalt component is increased, and the inlaid combination structure of the coking product is used for reducing the expansion rate of the prepared graphite negative electrode, so that the cycle performance of the graphite negative electrode can be remarkably improved, and the problems of deterioration of high-temperature storage performance and the like cannot be caused; the quinoline insoluble substance is a waste material generated in the asphalt refining process, the economic value is high, the whole technological process is simple, and the production cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of alkali metal ion batteries, and specifically provides a method for preparing a graphite negative electrode material, a negative electrode sheet and an alkali metal ion battery. Background Art

[0002] As one of the main materials of the battery cell, the negative electrode has a significant impact on the cycle performance of the energy storage battery cell. By reducing the expansion of the graphite negative electrode material, the consumption of active lithium due to SEI fragmentation and recombination during the cycle can be reduced. At the same time, the expansion stress during the cycle can be reduced, which is beneficial to its kinetic performance, reduces the risk of lithium plating during the cycle, and greatly improves its cycle performance.

[0003] At present, the methods to reduce the expansion of graphite anodes include amorphous carbon coating, reducing the particle size of graphite anodes, or isostatic pressing of graphite (increasing the orientation of graphite by batching, kneading and isostatic pressing). These modification methods are mostly process optimization, without improving the coke raw materials, and there are some obvious disadvantages. For example, amorphous carbon coating and reducing particle size can reduce the expansion of graphite, but will significantly deteriorate the high-temperature storage performance; and the isostatic pressing of graphite increases the orientation of graphite to reduce expansion, but the whole process is relatively cumbersome and the production cost is high.

[0004] It is necessary to develop a graphite negative electrode material that can significantly improve the cycle performance of the graphite negative electrode. The entire production process is simple and efficient, and will not cause deterioration of high-temperature storage performance. Summary of the invention

[0005] In order to overcome the above defects, the present invention provides a method for preparing a graphite negative electrode material, a negative electrode sheet and a battery.

[0006] In a first aspect, the present invention provides a method for preparing a graphite negative electrode material, comprising: mixing asphalt and quinoline insoluble matter to form an asphalt mixture; The asphalt mixture is subjected to heating treatment to obtain a graphite negative electrode material.

[0007] Furthermore, the softening point of the asphalt is 55-90°C.

[0008] Furthermore, the mass ratio of the asphalt to the quinoline insoluble matter is (80-90): (10-20).

[0009] Furthermore, the heating treatment of the asphalt mixture comprises: Processing the asphalt mixture at a preset pressure and a first preset temperature to obtain green coke; treating the raw coke at a second preset temperature to obtain pitch coke; A graphite negative electrode material is obtained based on the pitch coke.

[0010] Furthermore, the step of treating the asphalt mixture at a preset pressure and a first preset temperature to obtain green coke comprises: The asphalt mixture is heat treated at 1.5-2.0 MPa and 450-550° C. for 100 min-200 min to obtain green coke.

[0011] Further, the step of processing the raw coke at a second preset temperature to obtain pitch coke comprises: The raw coke is heat treated at 700-900° C. for 80 min-120 min to obtain pitch coke.

[0012] Furthermore, the graphite negative electrode material obtained based on the pitch coke comprises: The asphalt coke is crushed, shaped and graphitized to obtain a graphite negative electrode material.

[0013] Furthermore, the obtained graphite negative electrode material has a particle size D50 of 8.5-10.5 μm and a graphitization degree of 87%-91%.

[0014] In a second aspect, the present invention provides a negative electrode plate, comprising a negative electrode current collector, on which the graphite negative electrode material as described in the first aspect is coated.

[0015] In a third aspect, the present invention provides an alkali metal ion battery, comprising a battery housing, an electrolyte, a positive electrode plate, a separator, and the negative electrode plate as described in the second aspect, located in the battery housing.

[0016] The above one or more technical solutions of the present invention have at least one or more of the following beneficial effects: In the technical scheme for implementing the present invention, the present invention uses quinoline insoluble matter as an additive in the coking process to increase the quinoline insoluble matter content in the asphalt component, and adds an inlaid combination structure of the coke product to reduce the expansion rate of the prepared graphite negative electrode, which can significantly improve the cycle performance of the graphite negative electrode without causing problems such as deterioration of high-temperature storage performance.

[0017] In addition, quinoline insoluble matter is a waste material generated in the asphalt refining process, which has high economic value, and the entire process is simple and has low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The disclosure of the present invention will become more easily understood with reference to the accompanying drawings. It is easy for those skilled in the art to understand that these drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. In addition, similar numbers in the figures are used to represent similar components, among which: Figure 11. It is a schematic flow chart of the main steps of a method for preparing a graphite negative electrode material according to one embodiment of the present invention; Figure 2 is a schematic flow chart of main steps of obtaining graphite negative electrode material from asphalt mixture according to one embodiment of the present invention; Figure 3 This is a schematic diagram of optimizing the content of mosaic tissue in quinoline insoluble matter in the asphalt coking process according to an embodiment of the present invention. DETAILED DESCRIPTION

[0019] Some embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0020] The present invention provides a method for preparing a graphite negative electrode material, referring to Figure 1 ,include: S1, mixing asphalt and quinoline insoluble matter to form an asphalt mixture; S2, heating the asphalt mixture to obtain a graphite negative electrode material.

[0021] The present invention aims to solve the problem of rapid decay of cycle performance of graphite negative electrode due to excessive volume expansion during the cycle process. In order to achieve this goal, a certain amount of QI (Quinoline Insolubles) is added in the process of asphalt coking. By preventing the growth and fusion of interphase globules during the liquid phase carbonization process, the coke is helped to form more mosaic tissue structures, so that the graphite negative electrode material prepared by asphalt mixture production has a lower expansion rate. Such graphite negative electrode material performs well in cycle performance and can significantly improve the cycle stability of the battery. In addition, the entire production process is not only simple, but also efficient, and has good industrial application prospects.

[0022] In one embodiment, the quinoline insoluble matter is a waste material extracted during asphalt refining. The present invention requires mixing QI into asphalt before coking, and the added QI is a waste material extracted during asphalt refining, so the overall production cost is low and the economic value is high. This approach not only effectively utilizes materials that would otherwise be discarded, but also reduces environmental pollution, achieving a dual improvement in resource reuse and economic benefits.

[0023] In one embodiment, the asphalt is low temperature coal tar. More specifically, the softening point of the asphalt is 55-90°C.

[0024] In one embodiment, step S1 first weighs asphalt and quinoline insolubles according to a mass ratio of asphalt to quinoline insolubles of (80-90): (10-20), and then adds the asphalt and quinoline insolubles into a mixer and mixes them evenly.

[0025] In one embodiment, referring to Figure 2 , step S2, heating the asphalt mixture to obtain a graphite negative electrode material comprises: S21, treating the asphalt mixture at a preset pressure and a first preset temperature to obtain green coke; S22, treating the raw coke at a second preset temperature to obtain pitch coke; S23, obtaining a graphite negative electrode material based on the pitch coke.

[0026] In one embodiment, step S21, treating the asphalt mixture at a preset pressure and a first preset temperature to obtain green coke comprises: The asphalt mixture is heat treated at 1.5-2.0 MPa and 450-550° C. for 100 min-200 min to obtain green coke.

[0027] Through the above high temperature and high pressure reaction process, green coke is obtained from the asphalt mixture.

[0028] In one embodiment, step S22, treating the raw coke at a second preset temperature to obtain pitch coke comprises: The raw coke is heat treated at 700-900° C. for 80 min-120 min to obtain pitch coke.

[0029] Through the above-mentioned high temperature heat treatment, pitch coke is obtained from green coke.

[0030] Asphalt is a dark brown complex mixture of hydrocarbons of different molecular weights and their non-metallic derivatives. It is a kind of high-viscosity organic liquid. It is in liquid state, black on the surface, and soluble in carbon disulfide. Asphalt is an organic gelling material that is waterproof, moisture-proof and anti-corrosive.

[0031] Green coke is the residue obtained by deep cracking of petroleum residue, coal tar, asphalt and other raw materials by coking method. It is a porous coke material.

[0032] Pitch coke is the solid residue obtained after high-temperature dry distillation or delayed coking of coal tar.

[0033] In one embodiment, in step S23, obtaining a graphite negative electrode material based on the pitch coke comprises: The asphalt coke is crushed, shaped and graphitized to obtain a graphite negative electrode material.

[0034] In one application scenario, the crushing process includes: using a mechanical crusher to crush the asphalt coke into a target particle size.

[0035] The shaping process includes: using a shaping machine to grind and shape the edges of the crushed asphalt coke to improve the regularity of the particle morphology and reduce the edges of the particles; the graphitization treatment process includes: using a graphitization furnace to perform high-temperature heat treatment at 2800°C-3100°C on the shaped asphalt coke.

[0036] In one embodiment, the obtained graphite negative electrode material has a particle size D50 of 8.5-10.5 μm and a degree of graphitization of 87%-91%.

[0037] In one application scenario, the preparation method of the present invention first adds medium- and low-temperature coal tar and quinoline insolubles into a mixer according to a certain mass ratio and mixes them evenly to obtain an asphalt mixture; then, the asphalt mixture is added into a high-pressure reactor, and the high-pressure reactor is placed into a heating furnace for heating treatment to obtain green coke; then, the green coke is placed into a roasting furnace for high-temperature heat treatment to obtain asphalt coke with a fine mosaic structure; finally, the asphalt coke is subjected to crushing, shaping, and graphitization processes to obtain a low-expansion graphite negative electrode material.

[0038] The present invention also provides a negative electrode plate, comprising a negative electrode current collector, on which the graphite negative electrode material is coated.

[0039] The present invention also provides an alkali metal ion battery, comprising a battery casing, an electrolyte, a positive electrode sheet, a diaphragm and the negative electrode sheet located in the battery casing.

[0040] In one embodiment, the alkali metal ion batteries of the present invention include but are not limited to lithium ion batteries, sodium ion batteries and potassium ion batteries.

[0041] Next, the preparation method of the present invention is used to prepare graphite negative electrode material and manufacture negative electrode plates and batteries.

[0042] Example 1: A medium-temperature asphalt with a softening point of 80°C and quinoline insolubles were selected and mixed in a mass ratio of 85:15 to obtain an asphalt mixture; the asphalt mixture was then added to a high-pressure reactor, and the high-pressure reactor was placed in a heating furnace, heated to 500°C and heat-treated for 120 minutes to obtain green coke, during which the pressure of the high-pressure reactor was controlled at 1.8-2.0 MPa; the green coke was then placed in a roasting furnace, heated to 850°C and heat-treated for 100 minutes to obtain asphalt coke. The asphalt coke was then crushed, shaped, and graphitized to obtain a low-expansion graphite negative electrode material with D50=9.5μm and graphitization degree=89%.

[0043] The low-expansion graphite negative electrode material obtained in Example 1, SP (conductive carbon black), CMC (sodium carboxymethyl cellulose), and SBR (styrene-butadiene rubber) were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheet was obtained through coating, drying, rolling and other processes, and then assembled into a 2Ah soft-pack lithium-ion battery together with positive electrode sheets, electrolyte and other materials.

[0044] Example 2: A medium-temperature asphalt with a softening point of 65°C and quinoline insolubles were selected and mixed in a mass ratio of 85:15 to obtain an asphalt mixture; the asphalt mixture was then added to a high-pressure reactor, and the high-pressure reactor was placed in a heating furnace, heated to 500°C and heat-treated for 120 minutes to obtain green coke, during which the pressure of the high-pressure reactor was controlled at 1.8-2.0 MPa; the green coke was then placed in a roasting furnace, heated to 850°C and heat-treated for 100 minutes to obtain asphalt coke. The asphalt coke was then crushed, shaped, and graphitized to obtain a low-expansion graphite negative electrode material with D50=9.5μm and graphitization degree=89%.

[0045] The low-expansion graphite negative electrode material obtained in Example 2, SP, CMC, and SBR were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheet was obtained through coating, drying, rolling and other processes, and then assembled into a 2Ah soft-pack lithium-ion battery together with positive electrode sheets, electrolyte and other materials.

[0046] Example 3: A medium-temperature asphalt with a softening point of 80°C and quinoline insolubles were selected and mixed in a mass ratio of 90:10 to obtain an asphalt mixture; the asphalt mixture was then added to a high-pressure reactor, and the high-pressure reactor was placed in a heating furnace, heated to 500°C and heat-treated for 120 minutes to obtain green coke, during which the pressure of the high-pressure reactor was controlled at 1.8-2.0 MPa; the green coke was then placed in a roasting furnace, heated to 850°C and heat-treated for 100 minutes to obtain asphalt coke. The asphalt coke was then crushed, shaped, and graphitized to obtain a low-expansion graphite negative electrode material with D50=9.5μm and graphitization degree=90%.

[0047] The low-expansion graphite negative electrode material obtained in Example 3, SP, CMC, and SBR were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheet was obtained through coating, drying, rolling and other processes, and then assembled into a 2Ah soft-pack lithium-ion battery together with positive electrode sheets, electrolyte and other materials.

[0048] Example 4: A medium-temperature asphalt with a softening point of 80°C and quinoline insolubles were selected and mixed in a mass ratio of 85:15 to obtain an asphalt mixture; the asphalt mixture was then added to a high-pressure reactor, and the high-pressure reactor was placed in a heating furnace, heated to 500°C and heat-treated for 120 minutes to obtain green coke, during which the pressure of the high-pressure reactor was controlled at 1.5-1.8 MPa; the green coke was then placed in a roasting furnace, heated to 850°C and heat-treated for 100 minutes to obtain asphalt coke. The asphalt coke was then crushed, shaped, and graphitized to obtain a low-expansion graphite negative electrode material with D50=10.5μm and a graphitization degree=89%.

[0049] The low-expansion graphite negative electrode material obtained in Example 4, SP, CMC, and SBR were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheet was obtained through coating, drying, rolling and other processes, and then assembled into a 2Ah soft-pack lithium-ion battery together with positive electrode sheets, electrolyte and other materials.

[0050] Example 5: A medium-temperature asphalt with a softening point of 55°C and quinoline insolubles were selected and mixed in a mass ratio of 80:20 to obtain an asphalt mixture; the asphalt mixture was then added to a high-pressure reactor, and the high-pressure reactor was placed in a heating furnace, heated to 450°C and heat-treated for 200 minutes to obtain green coke, during which the pressure of the high-pressure reactor was controlled at 1.5-1.8 MPa; the green coke was then placed in a roasting furnace, heated to 900°C and heat-treated for 80 minutes to obtain asphalt coke. The asphalt coke was then crushed, shaped, and graphitized to obtain a low-expansion graphite negative electrode material with D50=8.5μm and graphitization degree=87%.

[0051] The low-expansion graphite negative electrode material obtained in Example 5, SP (conductive carbon black), CMC (sodium carboxymethyl cellulose), and SBR (styrene-butadiene rubber) were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheet was obtained through coating, drying, rolling and other processes, and then assembled into a 2Ah soft-pack lithium-ion battery together with positive electrode sheets, electrolyte and other materials.

[0052] Example 6: A medium-temperature asphalt with a softening point of 90°C and quinoline insolubles were selected and mixed in a mass ratio of 83:12 to obtain an asphalt mixture; the asphalt mixture was then added to a high-pressure reactor, and the high-pressure reactor was placed in a heating furnace, heated to 550°C and heat-treated for 100 minutes to obtain green coke, during which the pressure of the high-pressure reactor was controlled at 1.5-1.8 MPa; the green coke was then placed in a roasting furnace, heated to 700°C and heat-treated for 120 minutes to obtain asphalt coke. The asphalt coke was then crushed, shaped, and graphitized to obtain a low-expansion graphite negative electrode material with D50=9.5μm and graphitization degree=87%.

[0053] The low-expansion graphite negative electrode material obtained in Example 6, SP (conductive carbon black), CMC (sodium carboxymethyl cellulose), and SBR (styrene-butadiene rubber) were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheet was obtained through coating, drying, rolling and other processes, and then assembled into a 2Ah soft-pack lithium-ion battery together with positive electrode sheets, electrolyte and other materials.

[0054] Comparative Example 1: The artificial graphite powder after crushing and shaping is screened, and the artificial graphite powder with a particle size of ≤10μm is selected for standby use. 35kg of asphalt in a molten state at 200°C is added to 65kg of artificial graphite powder with a particle size of ≤10μm, and kneaded. The heating temperature of the kneading process is 250°C and the kneading time is 90min. All the kneaded raw materials are transferred to an isostatic pressing mold, evacuated to 40KPa, and then moved to an isostatic press for compression molding to obtain a green body. The green billet is placed in a crucible, and then the crucible is transferred to a vacuum roasting furnace. When the temperature rises from 100°C to 350°C, the heating rate is 1.0°C / h, when the temperature rises from 350°C to 600°C, the heating rate is 0.5°C / h, when the temperature rises from 600°C to 900°C, the heating rate is 1.5°C / h, and when the temperature rises from 900°C to 1300°C, the heating rate is 2.0°C / h. The calcined billet is graphitized, first heated to 1500°C, kept warm for 4h, then evenly heated to 2800°C, and finally cooled to 90°C at a cooling rate of 1.0°C / h to obtain a low expansion graphite material.

[0055] The low-expansion graphite negative electrode material obtained in Comparative Example 1, SP, CMC, and SBR were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheet was obtained through coating, drying, rolling and other processes, and then assembled into a 2Ah soft-pack battery together with the positive electrode sheet, electrolyte and other materials. The difference between Comparative Example 1 and the embodiment is only that the preparation process of the graphite negative electrode material is different, and other materials such as the positive electrode sheet, electrolyte, and the coating, drying, rolling and other processes are the same. The difference between Examples 1-6 is only that the parameters of the preparation process of the graphite negative electrode material are different.

[0056] The batteries prepared in the above examples and comparative examples were tested. The test items included: full charge expansion rate%, 1C / 1C at 25°C, 1000 cycle capacity retention rate%, and storage at 60°C for 100 days. Capacity retention rate %. The test results are shown in Table 1.

[0057] Table 1 Test results of batteries of embodiments and comparative examples

[0058] Through a detailed analysis of the test data in Table 1, it can be clearly observed that compared with Comparative Example 1, the embodiment shows a significant advantage in the full-charge expansion rate of the negative electrode. Specifically, under the same test conditions, the capacity retention rate of the negative electrode material of the embodiment not only did not show a significant decline after 1000 charge and discharge cycles, but was stably maintained at more than 96.7%. In contrast, the capacity attenuation of the battery in Comparative Example 1 was more obvious under the same conditions, and the capacity retention rate after 1000 cycles could only reach 94.3%. In addition, in the high-temperature storage test, the embodiment also showed higher thermal stability and longer service life. At a storage temperature of 60°C, after 100 days of storage, the battery capacity retention rate of the embodiment was still as high as more than 92.9%, while the battery in Comparative Example 1 showed a more obvious capacity attenuation, with a capacity retention rate of only 90.3%.

[0059] It can be seen that the full-charge expansion rate of the negative electrode of the embodiment is significantly lower, which indicates that the degree of volume expansion is small when it is charged to a fully charged state. The expansion rate is one of the important parameters for measuring the quality of the negative electrode material of a lithium-ion battery, and the negative electrode expansion rate is positively correlated with the cycle life of the battery. It is not only directly related to the cycle life of the battery, but also an important guarantee for battery safety. If the volume of the negative electrode material changes too much during the charging and discharging process, it is bound to cause irreversible damage to the internal structure of the battery, thereby affecting the number of cycles and overall performance of the battery. The low full-charge expansion rate shown in the embodiment is a direct reflection of the excellent performance of its negative electrode material, and a strong proof of its higher safety.

[0060] In order to more comprehensively evaluate the performance differences between the two negative electrode materials, a high-temperature storage test was also conducted. Under extreme conditions, that is, after being stored in a high-temperature environment of 60°C for 100 days, the battery of the embodiment once again showed superior performance, and its battery capacity retention rate remained strong, as high as 92.9% or more, and was less affected by the high-temperature environment. This result not only proves the stability of the material in a high-temperature environment, but also indicates its broad prospects in practical applications. In this test, the capacity attenuation of the battery in Comparative Example 1 was more obvious, and the capacity retention rate after 100 days of storage was only 90.3%. It can be seen that the battery of the embodiment has also been significantly improved in terms of cycle performance and high-temperature storage performance. These performance improvements are mainly attributed to the fact that the embodiment starts with optimizing the organizational structure of the coke raw material, by adding quinoline insolubles, increasing the proportion of fine mosaic organizational structure of the coke, and successfully preparing a graphite negative electrode material with good orientation and lower expansion rate. This graphite negative electrode material not only has higher structural stability, can effectively resist volume changes during charging and discharging, but also can maintain excellent performance in a high-temperature environment, providing solid support for the widespread application of lithium-ion batteries.

[0061] Compared with the graphite negative electrode optimization processes such as asphalt filling and coating in the comparative example, the processing technology of the embodiment of the present invention is simpler and more efficient. This simple and efficient processing technology not only significantly improves the cycle performance, but also performs well in high-temperature storage performance without deterioration. This shows that the embodiment of the present invention has unique advantages in optimizing the performance of graphite negative electrode materials, can effectively solve the problems existing in traditional processes, and provides a new idea and method for the preparation of graphite negative electrode materials.

[0062] In the coking process, the present invention skillfully utilizes quinoline insoluble matter QI as an additive, and optimizes the mosaic structure of the coke product by increasing the quinoline insoluble matter content in the asphalt component. Figure 3 As shown, the asphalt coke prepared by the present invention has a mosaic structure content of more than 80% and has good isotropy.

[0063] The present invention creatively uses the component QI, which is usually regarded as industrial waste in the prior art or the component QI that is usually considered to need to be removed, as an additive and adds it to the asphalt coking process in an appropriate doping amount. In traditional concepts, it is often regarded as useless because it is difficult to handle and may have an adverse effect on product quality. However, the present invention takes a unique approach and utilizes this "waste" to make it a key additive to improve the quality of asphalt coking through scientific formula design and process optimization. This unique approach can effectively prevent the growth and fusion of interphase globules during the liquid phase carbonization process in the asphalt coking process. Through this technical means, the coke raw material can form more mosaic tissue structures, so that the graphite negative electrode material produced from the coke raw material has a lower expansion rate and excellent cycle performance.

[0064] This innovative method significantly reduces the expansion rate of the prepared graphite negative electrode, thereby greatly improving the cycle performance of the graphite negative electrode. More importantly, this method does not lead to problems such as deterioration of high-temperature storage performance, ensuring the stability and reliability of the battery.

[0065] In addition, quinoline insolubles are actually waste materials generated during asphalt refining and have high economic value. Therefore, the present invention not only has significant advantages in technology, but also has high economic feasibility. The whole process is simple, the production cost is low, and it has good market application prospects.

[0066] It is worth noting that with the growing demand for high energy density and long life batteries in the fields of electric vehicles, energy storage systems, etc., the excellent performance exhibited by the batteries prepared using the negative electrode materials of the present invention will undoubtedly provide strong support for the development of these fields.

[0067] It should be pointed out that although the various steps in the above embodiments are described in a specific order, those skilled in the art can understand that in order to achieve the effects of the present invention, different steps do not have to be performed in such an order, and they can be performed simultaneously (in parallel) or in other orders. These changes are within the scope of protection of the present invention.

[0068] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

Claims

1. A method for preparing a graphite negative electrode material, characterized in that: include: mixing asphalt and quinoline insoluble matter to form an asphalt mixture; The asphalt mixture is subjected to a heating treatment to obtain a graphite negative electrode material; The heating treatment of the asphalt mixture comprises: Processing the asphalt mixture at a preset pressure and a first preset temperature to obtain green coke; treating the raw coke at a second preset temperature to obtain pitch coke; A graphite negative electrode material is obtained based on the pitch coke.

2. The method according to claim 1, characterized in that The softening point of the asphalt is 55-90°C.

3. The method according to claim 1, characterized in that The mass ratio of the asphalt to the quinoline insoluble matter is (80-90):(10-20).

4. The method according to claim 1, characterized in that: The step of treating the asphalt mixture at a preset pressure and a first preset temperature to obtain green coke comprises: heat treating the asphalt mixture at 1.5-2.0 MPa and 450-550° C. for 100 min-200 min to obtain green coke.

5. The method according to claim 1, characterized in that The step of treating the green coke at the second preset temperature to obtain pitch coke comprises: heat treating the green coke at 700-900° C. for 80 min-120 min to obtain pitch coke.

6. The method according to claim 1, characterized in that The method of obtaining the graphite negative electrode material based on the pitch coke comprises: subjecting the pitch coke to crushing, shaping and graphitizing treatment to obtain the graphite negative electrode material.

7. The method according to claim 1, characterized in that The obtained graphite negative electrode material has a particle size D50 of 8.5-10.5 μm and a graphitization degree of 87%-91%.

8. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector, on which the graphite negative electrode material according to any one of claims 1 to 7 is coated.

9. An alkali metal ion battery, characterized in that: It comprises a battery casing, an electrolyte, a positive electrode sheet, a separator and a negative electrode sheet as claimed in claim 8, which are located in the battery casing.

Citation Information

Patent Citations

  • Method for improving quality of prebaked anode

    CN101922020A

  • Preparation method of isotropic coke

    CN103693635A

  • Preparation method of microstructure graphite

    CN107265450A

  • Method for preparing high-performance graphite from asphalt

    CN115974064A

  • Isotropic coke as well as preparation method and application thereof

    CN118006352A